Influence of salinity on the dimethylsulphoniopropionate production from Prymnesium simplex - Dayala Vembilly Thariath; Dibu Divakaran; Sujatha Chenicherry (Sustainable Environment Research, 2019)
Abstract Dimethylsulphoniopropionate (DMSP) is a tertiary sulphonium compound which has received a considerable attention over recent years for acting as a principal intermediate in the production of dimethylsulphide, which is mostly noted as odour causing substance and it acts as a potential key player for climate regulation. The synthesis of DMSP is confined to some species of microalgae especially, prymnesiophytes and dinophytes and its concentration level varies with some environmental factors. In this context, this research work applies an experimental approach to assessing the production rate of DMSP under varying salinity (28, 30, 32 PSU) across distinctive growth phases. For this purpose, estuarine isolated microalgae, Prymnesium simplex (prymnesiophyceae) was selected as a model organism. The results showed that the growth rate response of P. simplex was significantly reduced at lower salinity (28 and 30 PSU) compared to higher salinity in this range (32 PSU). The concentration of DMSP and particulate fraction of DMSP was also elevated at higher salinity in the exponential phase of growth and lower at lower salinity. In contrast, the maximum production of dissolved DMSP was seen at lower salinity. Essentially research is to determine a maximum contribution of the regionally important prymnesiophyte family in the process of biogeochemical sulphur cycling.